Clinical Characteristics and Long-Term Mortality Rate in Female Patients with Takotsubo Syndrome Compared with Female Patients with ST-Elevation Acute Myocardial Infarction: A Retrospective Study from a Single Center. (30th July 2019) - Massobrio, Laura; Valbusa, Alberto; Sartini, Marina; Meliota, Giovanni; Cavalla, Francesca; Miceli, Roberta; Vischi, Giulia; Cristina, Maria Luisa; Spagnolo, Anna Maria; Delfino, Roberto; Abbadessa, Francesco; Porto, Italo; et al.
Abstract : Background . Takotsubo syndrome (TTS) is characterized by acute transient, stress-induced, left ventricular systolic dysfunction, generally presenting with apical ballooning. It can mimic an acute coronary syndrome, but with a milder increase in cardiac enzymes and without culprit coronary artery disease on angiography. Data on long-term follow-up and survival in patients with TTS, compared with patients with ST-elevation myocardial infarction (STEMI), are scarce. Purpose . To assess all-cause mortality rate and survival in a consecutive series of female patients with TTS compared with age- and sex-matched STEMI patients on long-term follow-up. Methods and Results . We collected data of 65 TTS female patients (TTS group) with a mean age of 73.42 ± 11.35 years from 2001 to 2013. Collection of follow-up information was concluded for all patients in 2016. To compare the mortality and survival of TTS patients with those of the STEMI population, we used data from our STEMI Registry, a prospective registry of 7446 STEMI patients admitted from 2001 to 2013 to our cath-lab for primary percutaneous coronary intervention (p-PCI). From the registry, we selected 104 STEMI patients (STEMI group) comparable to our TTS group in terms of age (mean age of 72.33 ± 11.92 years) and sex. On follow-up examination after a median of 1000 days, the TTS group had a lower all-cause mortality rate than the STEMI group (7.69% versus 23.08%). This difference was statistically different between the two groups (log-rank test, p value = 0.03). Conclusions . In our study, TTS and STEMI patients displayed a statistically significant difference in long-term survival. Specifically, the TTS group had a lower mortality rate than the STEMI group. This seems to suggest that TTS and STEMI are two different clinical entities with two different clinical outcomes.